(3JRjjf GdCQGFc HEQSGd GdfHi Edi GdedGFcs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3SdjeGf Hf eMeO SMdhd GdEOdHi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg CSJYjf hCcJai , hCSCdg GddWa GdNai SFd GdYdGeI GdLdGd GdSjhWi Yf bhd GdYdeGA Efg Udi Gddg Ydgj hSde de jHYK Edi GdedGFcI hbhd GdMGaX Rjf GdYQGbi Ef GdSeGA djSJ eMdkG ddJcdja s
(3BNQgG (B:s
(3NGJeI ai cTa GdCSQGQ dGHf GdYeGO McGjI Cf BOe CQSd Edi GdedGFcI djfHFge HeG Yde ef GdCSeGA aEf UM Pdc cGf CMO GdCOdI Ydi EQSGdg Udi Gddg Ydjg hSde Edjge heef fU YdjgG GdEeGe GdTGaYi QVi Gddg Yfg hGQVGg Je HYhf Gddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3Ydi gGeT GdQSGdI HYV GdahGFO s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJhMjO hGdedd hGdfMds